Examples of finite-dimensional Hopf algebras with the dual Chevalley property - Andruskiewitsch, Nicolas (2017)
We present new Hopf algebras with the dual Chevalley property by determining all semisimple Hopf algebras Morita-equivalent to a group algebra over a finite group, for a list of groups supporting a non-trivial finite-dimensional Nichols algebra.